PTU-074 Infection and history of infection are independent of meld for prognosis in cirrhosis. (23rd September 2015) - Tsami, A; Tsochatzis, E; Arvaniti, V; Garcovich, M; Isgro, G; O'Beirne, J; Burroughs, A
Abstract : Introduction: Bacterial infections are common in cirrhosis and have significant mortality. MELD excludes complications as adding to prognosis in cirrhosis. We evaluated patients with cirrhosis plus/minus infection to assess if infection added prognostic information to MELD. Methods: Consecutive cirrhotics with first admission to hospital between 2007 and 2009. MELD scores (and other parameters) were collected at baseline. Infection was defined as positive bacterial culture at admission or during first hospitalisation. Possible infection was defined as patients receiving antibiotics during first hospitalisation. Mortality at 3 and 12 months was evaluated by multiple logistic regression using MELD parameters and infection/possible infection. Results: 334 cirrhotics, 222 males (66.5%), mean age 53.8±11.6 years. Infection was present in 78 (23.4%) and possible infection in 179 (54%). There were 36 deaths in 3 months and 48 in 12 months. Mean Child-Pugh and MELD scores were 8.6±2.5 and 16.2±6.9, respectively. 1-year mortality was independently associated with proven infection (OR 4.26, 95% CI 1.98 to 8.91, p<0.001), bilirubin (OR 1.003 P=0.038) and INR (OR 2.11, p=0.04). 3-month mortality was independently associated with proven infection (OR 4.92, 95% CI 2.23 to 10.86, p<0.001) and INR (OR 2.39, CI 95%, p=0.01). Suspected infection was independently associated with both 1-year (OR 2.83, 95% CI 1.21 to 6.60, p=0.02) and 3-month mortality (OR 4.89, 95% CI 1.61 to 14.84, p=0.005). When patients who died within 1 month (n=19, dying due to infection/other causes) were excluded to assess if the history of infection (once treated) still added to prognosis, one year mortality was independently associated with proven infection (OR 2.66, 95% CI 1.09 to 6.47, p=0.03) and creatinine (OR 1.007, p=0.03). When analysis was repeated with suspected infection, then it was marginally associated to 1-year survival (P=0.054). Conclusion: Infection adds to MELD for prognosis at 3 and 12 months in cirrhotics admitted to hospital. Recovery from treated infection still confers independent prognostic value to MELD so that MELD is not independent of infection for prognosis in cirrhosis. The influence of other complications on MELD need revisiting.